Changes in some soil chemical properties in peatland after two years of fire in Kubu Raya, West Kalimantan: Changes in some soil chemical properties in peatland - Hartono, Arief; Rusdiana, Omo; Pulunggono, Heru Bagus; Simanihuruk, Denis Muba Pandapotan; Saputra, Ilham (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2022)
Peatland fire that occurred in 2018 are located in Kubu Raya Regency, West Kalimantan. The fire was claimed to cause the changes leading to peatland damage. The initial study based on samples collected in fire period reported that there were some changes of chemical properties leading to peatland damage. The study aimed to evaluate the effect of land fires on changes in some soil chemical properties after two years of fires. Soil samples of fired and unfired peatland were subjected to soil analyses. Soil analyses covered soil pH, organic carbon (C), phosphorus (P), calcium (Ca), magnesium (Mg), potassium (K), iron (Fe), manganese (Mn), copper (Cu), zinc (Zn), and bulk density (BD). The results showed that after two years of peatland fires did not affect the changes of peat soil pH, organic C, P, Ca, Mg, K, Cu, Zn, Mn and BD. One plot of fired peatland showed that the weight of frond and leaf area of oil palm grown on it was not statistically different from those of unfired peatland. The results suggested some chemical properties return to previous equilibrium due to high buffering capacity of peat soil.